ANALYSIS OF THE FINANCIAL PERFORMANCE OF THE INSURANCE COMPANY BINA DANA ARTA TBK IN THE ERA OF DIGITALIZATION - Nurazizah; Raju Maulana; Muhammad Fauzan (Indragiri Research Center (ingreat), 2026)
This study aims to analyze the financial performance of PT Asuransi Bina Dana Arta Tbk in the era of digitalization by using liquidity ratio and profitability ratio. This study uses a quantitative descriptive method with secondary data in the form of the company's financial statements for 2023 and 2024. The data analysis technique is carried out through the calculation of financial ratios consisting of Current Ratio, Cash Ratio, Return on Assets (ROA), and Return on Equity (ROE). The results of the study show that the company's financial performance has declined from 2023 to 2024. In terms of liquidity, the Current Ratio decreased from 9.96 to 2.43, while the Cash Ratio decreased from 6.92 to 0.38. This condition shows that the company's ability to meet short-term obligations is still quite good, but the availability of cash has decreased significantly. In terms of profitability, ROA decreased from 0.94% to -1.28%, while ROE decreased from 1.60% to -2.30%. This shows that the company has not been able to optimize its assets and equity to generate profits. Thus, the financial performance of PT Asuransi Bina Dana Arta Tbk in the digitalization era still needs to be improved, especially through cash management, operational efficiency, burden control, and the use of digital technology more effectively.